The software challenge for the next decade: the global objects scenario - Leao, Beatriz de Faria [UNIFESP] (1998)
This paper discusses the advantages of developing software as pattern-based components. The design and implementation of a pattern-based suite of software components specially constructed for the electronic patient record is presented. The methodology and the lessons learned in the development of these components are discussed Finally, some comments about the globalization and the need for more integration among component developers in a worldwide basis is discussed.